Marketing agility in volatile, uncertain, complex and ambiguous (VUCA) contexts: a systematic literature review and future research agenda - Yogesh Dwivedi (Management Review Quarterly, 2023)
Firms increasingly need to be customer-focused and adaptable to changing markets. Marketing agility (MA), a dynamic capability, supports an organization to respond to market changes faster, often resulting in performance benefits. While MA provides advantages in volatile, uncertain, complex, and ambiguous (VUCA) contexts, limited research exists that inform MA conceptualization and practice in VUCA contexts. Furthermore, conceptualization of MA has resulted in many, often overlapping, constructs. In this review, we searched four databases and used snowballing to arrive at a corpus of 27 articles. The corpus is summarised using the theory–context–characteristics–methodology framework, with an emphasis on practical implementation. From our findings, we offer propositions in response to our research question that addresses an important research gap, and future research directions are discussed. We advance theory and offer conceptual clarity by finding that MA in VUCA contexts may be reimagined using seven overarching constructs and summarizing extant literature that will benefit academics and practitioners.